PdII‐Catalyzed Mild CH ortho Arylation and Intramolecular Amination Oriented by a Phosphinamide Group. Issue 12 (23rd February 2014) - Guan, Jing; Wu, Guo‐Jie; Han, Fu‐She
Abstract A novel protocol for the Pd‐catalyzed ortho‐arylation of aryl phosphinamide with boronic acid is reported. By using phosphinamide as a new directing group, the reaction proceeds efficiently under mild conditions at 40 °C. Mechanistic studies reveal that the reaction proceeds via a PdII to Pd0 cycle. The phosphinamide group is also shown to be an effective orienting group for direct CH amination.